Mathematical model of heat transfer and feasibility test of improved cooking stoves in Bangladesh. Issue 3 (3rd April 2019) - Masud, M. H.; Ahamed, Raju; Joardder, Mohammad U. H.; Hasan, Mehide
ABSTRACT: Improved cooking stoves (ICSs) advance the cooking system significantly in Bangladesh. However, the comparative performance analyses of ICSs of Bangladesh are not available in the literature. In this study, heat loss through the stoves was investigated by using ANSYS simulation. From the simulation result, it was found that the average temperature of the wall of ICSs was less than the conventional stove. The maximum thermal efficiencies of some ICSs were found 30%, which is better than other conventional stoves. In addition to this, a feasibility study of ICSs has been carried out by considering cost, greenhouse gas emission and effectiveness of the ICSs. Taken all into consideration, this study would contribute to the literature for further improvement of the stove and guide the consumer to select the appropriate ICS.